Chinese Foreign Language Learners' Knowledge of Chinese Culture and the Influences of Linguistic Proficiency, Learning Experiences, Cultural Background and Other Contributing Factors on Their Knowledge Levels - Ha, Minyeong (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2026)
This thesis examines Chinese as a Foreign Language (CFL) learners' knowledge of Chinese culture and the extent to which this knowledge is shaped by linguistic proficiency, learning experiences, cultural background, and a range of additional contributing factors. In doing so, it addresses a central concern in language and intercultural education, namely that language learning extends beyond the acquisition of grammar and vocabulary to involve engagement with sociocultural contexts, identity negotiation, and culturally situated meaning-making. The study was conducted in three phases. It began with a scoping review that mapped research on CFL learning over a period of more than two decades, identifying key patterns and gaps in the literature relating to cultural knowledge acquisition. Building on this foundation, the study then employed a quantitative survey design to investigate learners' reported knowledge of 36 elements of Chinese culture, with data analysed using IBM SPSS Statistics (version 29) through descriptive statistics, correlation analyses, independent samples t-tests, ANOVA, and multiple regression analysis. The findings indicate that while multiple factors contribute to variations in cultural knowledge, Chinese language proficiency (HSK level) constitutes the most significant predictor. In addition, learners from Asian cultural backgrounds that share elements of the Chinese macrosystem demonstrate relatively higher levels of cultural knowledge even at lower levels of linguistic proficiency, suggesting the influence of broader sociocultural alignment. The duration of Chinese language study is also associated with increased knowledge levels, alongside a range of experiential and relational factors, including learning approaches, visits to China, participation in cultural events, interpersonal relationships with Chinese individuals, and identification with Chinese heritage. Interpreted through the combined lenses of Linguistic Relativity, Sociocultural Theory, and the Bioecological Systems Theory, these findings highlight the interaction between cognitive, social, and environmental dimensions in shaping cultural knowledge acquisition. The findings suggest that effective CFL education is strengthened when linguistic development is integrated with opportunities for meaningful cultural engagement, including both physical immersion and digitally mediated experiences. This highlights the importance of designing curricula that incorporate both traditional and contemporary cultural content, supporting learners in developing more nuanced and contextually grounded knowledge of Chinese culture.
APPROVED
Keywords: Chinese as a Foreign Language (CFL); Cultural Knowledge; Chinese Culture; Linguistic Proficiency; HSK; Intercultural Competence; Sociocultural Theory; Bioecological Systems Theory; Linguistic Relativity; Cultural Background; Learning Experiences; Cultural Immersion